An Evaluation of Support Services for Students with Special Needs in Islamiyah School in Southwest Nigeria - Yahya, Isiaq Oluwatosin; Owoyale-Abdulganiy, Ibrahim Solahudeen; Raheed, Azeez Olalekan; Abiola, Muhydeen Olaitan (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study investigates the availability, effectiveness, and impact of support services for students with special needs in Islamiyah schools in Southwest Nigeria. Despite growing attention to inclusive education, many students with disabilities still face difficulties in transitioning through school and completing their education. Significant challenges include limited access to specialized support services, inadequate teacher training, and weak inclusive education policies. Although resources such as assistive technology, counselling, and specialized educational support exist, their implementation in Islamiyah schools is inconsistent and often dependent on external aid. Using a Convergent Parallel Design, the study collected quantitative and qualitative data from 17 Islamiyah schools through questionnaires and focus group discussions with teachers, school administrators, students with special needs, parents, and community leaders. Quantitative data were analyzed with SPSS, while qualitative insights were obtained through thematic analysis. The study's findings indicate that support services are inadequate and uneven, with urban schools generally better prepared than rural ones. The study highlights crucial factors for the educational success of students with special needs, such as family support, personal motivation, peer relationships, easy access to learning materials, and community involvement. The study emphasizes the need for policy reform, increased investment, and stronger stakeholder collaboration to improve inclusive practices in Islamiyah schools.